Tinjauan Yuridis Undang-Undang Nomor 11 Tahun 2020 Tentang Cipta Kerja Terhadap Perubahan Substansi Analisis Mengenai Dampak Lingkungan - Fauzan Ramon (Yuriska: Jurnal Ilmiah Hukum, 2021)
Background: Law No. 11 of 2020 on Job Creation has many inaccuracies in both the procedure of formation and its content material, thus causing problems in the environmental sector and the possibility of weakening environmental protection efforts. Comparative analysis of Law No. 11 of 2020 on Job Creation to Law No. 32 of 2009 on Environmental Protection and Management, especially in catchall Articles that are considered detrimental to the community as an effort to weaken environmental protection. Research Methods: This research was a normative juridical study, which compares old provisions with new provisions and tried to describe the shortcomings or advantages of the removal or amendment of articles in the previous Law by using several approaches adjusted to the object and purpose of the research. This study used the statute approach1 which was Law No. 11 of 2020 on Job Creation and Law No. 32 of 2009 on Environmental Protection and Management. Besides, the author also used a comparative approach and conceptual approach. Findings: The impact of the elimination and amendment of articles in Law No. 32 of 2009 on Environmental Protection and Management by Law No. 11 of 2020 on Job Creation is classified into 3 fundamental things, such as, the reduction of community participation to protect the environment, the weakening of law enforcement, one of them is due to the elimination of the principle of strict liability, and the strengthening of the authority of the central government to explore environment that also indirectly weakens the authority of the region to protect the environment belonged to its authority. Conclusion: Comparison of Law No. 11 of 2020 on Job Creation and Law Number 32 of 2009 on Environmental Protection and Management lies on 3 major issues, such as; First, the removal of environmental permits which is then replaced with the term environmental approval which certainly removes the terms, measures, and mechanisms of environmental permits. Second, the change in the substance of Environmental Impact Assessment (Amdal), and the third is the change of the principle on waste management from the principle of strict liability to the principle of liability based on fault.